Factors associated with radiographic progression in rheumatoid arthritis starting biological diseases modifying anti-rheumatic drugs (bDMARDs) - Giovanni Adami; Angelo Fassio; Francesca Pistillo; Camilla Benini; Ombretta Viapiana; Maurizio Rossini; Davide Gatti (Therapeutic Advances in Musculoskeletal Disease, 2023)
Background: Biological DMARDs (bDMARDs) have been proven to prevent joint damage and bone erosions. Nevertheless, approximately 15% of rheumatoid arthritis (RA) patients on bDMARDs will progress despite good control of joint inflammation. Objectives: The objective of our study is to investigate the factors associated with radiological progression of patients treated with bDMARDs. Design: We conducted a retrospective analysis of longitudinally collected data on RA patients starting bDMARDs. Methods: Presence or development of new erosions was assessed by a skilled rheumatologist at the time of the visit (baseline and 12 months thereafter). To determine the predictors of erosions, we employed multivariable logistic regression models. Discriminatory capacity for the prediction of new erosion development was assessed with receiver operating characteristic (ROC) curve, which was based on the logistic regression model. Results: A total of 578 RA patients starting bDMARDs were included in the study. Overall, 46 patients (approximately 10%) had radiographic progression (at least one new erosion) at 12 months of follow-up. The factors independently associated with higher risk of developing new erosions while on bDMARD were younger age, high disease activity at baseline, not being treated with cDMARDs, and presenting with erosions at baseline. In addition, we built a predictive model that can accurately foresee new erosions (AUC 0.846) in patients receiving bDMARDs Conclusion: We found that baseline erosive disease, higher disease activity during treatment, younger age, and monotherapy were the factors independently associated with the development of bone erosions. Our study may inform future targeted intervention in RA patients at risk of radiographic progression.